Bak, Joan Lamaysou. Some antecedents of corporatism: state economic intervention and rural organization in Brazll. The case of Rio Grande do Sul, 1890-1937. Yale University, 1977 (tese de doutoramento). - Gertz, René E. (Estudos Ibero-Americanos, 1983)
-